Sustainable development of human settlements : achievements and challenges in housing and urban policy in Latin America and the Caribbean. - Mac Donald, Joan...[et al] (UN ECLAC, 2011)
Examines aspects such as urban management and equity; managing urban land; the provision of housing and housing technology; environmental management and infrastructure; and sustainable development of human settlements.
http://www.eclac.org/publicaciones/xml/5/4725/l-1106-i.pdf
Keywords: HUMAN SETTLEMENTS; HOUSING; URBAN POLICY; SUSTAINABLE DEVELOPMENT; URBAN LAND; ENVIRONMENTAL MANAGEMENT; LATIN AMERICA; CARIBBEAN